Marine Microbial Ecology: A Comprehensive Review of Interactions, Symbiosis, and Bioprospecting. - Mukesh Chander* (International Journal of Marine Life, 2026)
Marine microorganisms constitute the largest and most dynamic fraction of Earth's biodiversity, governing vital ecosystem functions ranging from global biogeochemical cycling to host-specific symbiotic associations. This review provides a comprehensive synthesis of the complex interaction networks within marine microbial communities. We first explore the theoretical foundations of microbial niche construction and evolutionary dynamics in the ocean. Subsequent sections dissect micro-scale interactions within the phycosphere, where chemical gradients dictate cross-kingdom mutualisms and antagonisms, including novel inorganic signaling pathways that trigger algal bloom collapse. At the macro-ecological scale, we examine the intricate dissolved organic matter (DOM) recycling loops within coral reef ecosystems, highlighting how microbial metabolism sustains high gross primary productivity in oligotrophic waters. Furthermore, this review critically assesses the destabilizing impacts of anthropogenic climate change, ocean acidification, and aquaculture on microbiome stability, emphasizing the 2 transition from healthy holobionts to states of dysbiosis. Finally, we highlight the immense biotechnological potential of marine bioprospecting, detailing how unique microbial adaptations in extreme environments, unlocked via advanced multi-omics technologies, are driving unprecedented innovations in the pharmaceutical, industrial, and environmental sectors.
Keywords: Dissolved organic matter; Keywords: Aquatic ecosystem; Marine Ecology; Microbes; Phycosphere